The role of cold adaptation in cryopreservation of Dunaliella salina Teod. microalgae - Chernobai, Nadiia; Kadnikova, Nataliya; Kovalenko, Igor (Advances in Biology & Earth Sciences Vol.4, No.2, 2019, pp.119-127, 2019)
The main aim of this work was to investigate the effect of cold exposure on the potential for the synthesis of certain cellular products of industrial interest with the unicellular green alga D. salina Teod., and to study of the effect of cold adaptation on the preservation of cells during freeze-warming. It was shown that cold adaptation stimulates the formation of intracellular lipid globules and the synthesis of β-carotene, which increases the safety of cells grown on a depleted medium and frozen at a slow rate (1deg/min). Rapid cooling to -196 °C was lethal for D. salina Teod. cells.
Nadiia Chernobai, Nataliya Kadnikova, Igor Kovalenko The role of cold adaptation in cryopreservation of Dunaliella salina Teod. microalgae. Advances In Biology and Earth Eci, 2019. Vol. 4, № 2. p. 119-127.
Keywords: microalgae; Dunaliella salina; stress factors; cold adaptation; cryopreservation; glycerol; β-carotene